2006
DOI: 10.1177/1070496506294635
|View full text |Cite
|
Sign up to set email alerts
|

Political Deadlock and Devolved Wildlife Management in Zimbabwe

Abstract: Since February 2000, Zimbabwe has been experiencing an unparalleled period of political, economic, and social uncertainty. The most prominent features are the political deadlock generated by (a) confrontation between the ruling Zimbabwe African National Union–Patriotic Front (ZANU-PF) and the Movement for Democratic Change (MDC) party; (b) the illegal invasion of private land; (c) hyperinflation; and (d) the withdrawal of bilateral donor funds. Generally, a culture of impunity exists that compromises the rule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 1 publication
2
23
0
Order By: Relevance
“…From speaking with community members and reviewing archival sources, evidence suggests the dictatorial tendencies of the Headman and the subtle imposition by the Chief, affected locals perception of the CAMPFIRE program. In addition, the personalization of CAMPFIRE benefits has been a commonly observed trend in other CAMPFIRE programs (Mapedza & Bond, 2006;Rihoy, Chirozva, & Anstey, 2010). The collapse in governance in Masoka was due to the loss of external protection plus, the culture of impunity, and re-exertion of personalized rule at national and local levels in Zimbabwe post 2000 trumped what the people liked, wanted, and allowed the re-exertion of personalized rule to play out at local level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From speaking with community members and reviewing archival sources, evidence suggests the dictatorial tendencies of the Headman and the subtle imposition by the Chief, affected locals perception of the CAMPFIRE program. In addition, the personalization of CAMPFIRE benefits has been a commonly observed trend in other CAMPFIRE programs (Mapedza & Bond, 2006;Rihoy, Chirozva, & Anstey, 2010). The collapse in governance in Masoka was due to the loss of external protection plus, the culture of impunity, and re-exertion of personalized rule at national and local levels in Zimbabwe post 2000 trumped what the people liked, wanted, and allowed the re-exertion of personalized rule to play out at local level.…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of this paper thus, is to illustrate how the changing macro and meso levels can serve as cues for the elite to capture community projects. Previous studies show how national political process contribute to the decline in local level governance but do not provide specific mechanisms that enabled local elites to destroy local level participatory processes (Mapedza and Bond, 2006;Mashinya, 2007;Rihoy et al, 2007). We seek to explore this power dynamic in a more nuanced way.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Financial difficulties led to challenges in purchasing ammunition for controlling problem animals and obtaining resources for responding to problem animals, and resulted in RDCs reducing the proportion of revenue they gave back to the CAMPFIRE communities (Mapedza 2009). The economic collapse in Zimbabwe, high inflation, and the withdrawal of the donor community following the land reforms since 2000 have been reported to have eroded the benefits that most conservation programs derive from the communal areas, given that payments of household cash dividends from CAMPFIRE revenue activities take place six months to a year after the activities have occurred (Mapedza and Bond 2006, Rihoy and Mugaranyanga 2007, Fischer et al 2011. For instance, in 1999, each household in the Mahenye community received an average earning of US$59 (Vorlaufer 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that successful or effective community-based natural resources management programs, such as CAMPFIRE, would be associated with reduced human-wildlife conflicts as a result of (i) the devolution of wildlife management to local people; (ii) a high response to incidences of human-wildlife conflicts, which would mitigate wildlife-induced damages in the community; and (iii) the high education and environmental awareness of local people on how to minimize risk or damage from wild animals (e.g., Woodroffe et al 2005, Mapedza andBond 2006). However, in certain cases where human-wildlife conflicts were on the rise due to increasing animal populations and unsatisfactory response by responsible authorities, human-wildlife conflicts have been reported as undermining what have been, to date, quite successful CAMPFIRE programs (Mutandwa and Gadzirayi 2007), given that the Parks and Wildlife Act of 1975, Zimbabwe, does not have provisions for direct compensation for losses from wildlife.…”
Section: Introductionmentioning
confidence: 99%
“…Past policies and many development projects are based on the assumption that community-based or private conservation initiatives will help reduce poverty while maintaining wildlife populations. In reality, the benefits from such initiatives are often limited, and there is gathering evidence that these assumptions are unrealistic -both in terms of increasing wildlife populations and reducing poverty [22][23][24][25]. In fact, most wildlife populations across Kenya have declined considerably over the last 30 years despite the work of numerous governments, non-government organizations (NGOs), entrepreneurial initiatives, and scientific research efforts [26,27].…”
Section: Socio-ecological (Ses) Setting: Identifying Participantsmentioning
confidence: 99%